2013
DOI: 10.1590/s0104-42302013000600008
|View full text |Cite
|
Sign up to set email alerts
|

Análise das arteriografias de diabéticos e não diabéticos com isquemia crítica da perna

Abstract: ARTIGOS ARTIGOS ORIGINAIS _____________ A B S T R A C TObjective: To compare angiographic findings of diabetic and nondiabetic patients with critical limb ischemia. Methods:We included 161 patients with infrainguinal critical limb ischemia (CLI). We evaluated the clinical and arteriographic (number and presence of opacification of leg arteries) of the two groups of patients. Statistical analysis was performed using EPI-INFO.Results: Most patients were category 5 of Rutherford's Classification and had femoropop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Atherosclerosis is a complex systemic disorder where coronary risk factors, such as hypertension, dyslipidemia, T2DM, and smoking, have important pathophysiological roles [28, 29]. Current reports have demonstrated that the initiation of atherosclerosis involves a dynamic inflammatory activity, and not just an inert vascular injury instigated by blood lipoproteins and other elements on the arterial wall [30, 31]. Also, white blood cells have a key participation in this inflammatory course [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is a complex systemic disorder where coronary risk factors, such as hypertension, dyslipidemia, T2DM, and smoking, have important pathophysiological roles [28, 29]. Current reports have demonstrated that the initiation of atherosclerosis involves a dynamic inflammatory activity, and not just an inert vascular injury instigated by blood lipoproteins and other elements on the arterial wall [30, 31]. Also, white blood cells have a key participation in this inflammatory course [32, 33].…”
Section: Discussionmentioning
confidence: 99%